Designed Rain Analysis of Various Times Using the Gumbel Method in The Babak River Flow Area, West Lombok District - Yamin, Muhamad; Zamah Sari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Babak River is located in Bagu Village which is part of the Administrative Region of Pringgarata District, Central Lombok Regency, which is one of the areas where river flooding and drainage systems frequently occur. In analyzing the planned flood discharge of the Babak river by evaluating several parameters including daily maximum rainfall, planned rainfall, effective rainfall, planned flood unit hydrograph. The purpose of the planned flood discharge analysis is to evaluate the magnitude of the planned flood discharge at various return periods. Based on the background, the problem formulation in this research is to find out the magnitude of the base flow in the river basin and the magnitude of the planned flood discharge at various return periods of T years. After analyzing the rainfall data obtained at the BMKG (Meteorology and Geophysics Agency) West Lombok Regency office, the rainfall plan for various return periods using the Gumbel method is as follows: 2 years = 444,687; 5 years = 477,295; 10 years = 498.909 mm; 20 years = 519.342 mm; 25 years = 526.192 mm; 50 years = 546.424 mm; 100 years = 566.542 mm. Based on the Babak Watershed Characteristics data and data analysis, it was obtained that the base flow discharge in the Babak Weir River Gebong River area, Central Lombok Regency was = 5,289 m3/sec